Seasonal modulation of mesoscale processes alters nutrient availability and plankton communities in the Red Sea. (April 2019) - Kürten, Benjamin; Zarokanellos, Nikolaos D.; Devassy, Reny P.; El-Sherbiny, Mohsen M.; Struck, Ulrich; Capone, Douglas G.; Schulz, Isabelle K.; Al-Aidaroos, Ali M.; Irigoien, Xabier; Jones, Burton H.
Highlights: Mesoscale activity alters plankton metabolism and export. Stratification stimulates diazotrophic and heterotrophic plankton. Seawater oxygen isotopes trace the advection of GASW. Mesoscale eddies entrain GASW into the surface circulation. Eddies and GASW stimulate autotrophic plankton. Abstract: Hydrographic and atmospheric forcing set fundamental constraints on the biogeochemistry of aquatic ecosystems and manifest in the patterns of nutrient availability and recycling, species composition of communities, trophic dynamics, and ecosystem metabolism. In the Red Sea, latitudinal gradients in environmental conditions and primary production have been ascribed to fluctuations in Gulf of Aden Water inflow, upwelling/mixing, and regenerated nutrient utilization i.e. rapidly recycled nitrogen in upper layers. However, our understanding of upper layer dynamics and related changes in plankton communities, metabolism and carbon and nitrogen export is limited. We surmised that stratification and mesoscale eddies modulate the nutrient availability and taxonomic identity of plankton communities in the Red Sea. Based on remote-sensing data of sea level anomalies and high resolution in situ measurements (ScanFish) we selected stations for hydrographic CTD profiles, water sampling (nutrients, seawater oxygen stable isotopes [δ 18 OSW ]), phytoplankton and zooplankton collections. In fall 2014, strong stratification subjected the plankton community to an overall nitrogen and phosphorus shortage. The nutrient deficiency increased numbers of heterotrophic dinoflagellates, microzooplankton, and diazotrophs ( Trichodesmium, diatom-diazotroph associations [DDAs]), albeit largely decreased phytoplankton and mesozooplankton abundances. In spring 2015, mesoscale eddies increased the nutrient availability, and the thermohaline characteristics and low δ 18 OSW point to the interaction of eddies with Gulf of Aden Surface Water (GASW). Cyclonic eddies and, most likely, the availability of nutrients associated with the GASW, increased the abundances of autotrophs (diatoms, Prasinophytes) and supported larger numbers of zooplankton and their larvae. We demonstrate that the interplay of stratification, advection of Gulf of Aden water and mesoscale eddies are key elements to better understand changes in plankton community composition, ecosystem metabolism, and macronutrient export in the Red Sea in space and time.